Good Functional Outcome after Prolonged Postanoxic Comatose Myoclonic Status Epilepticus in a Patient Who Had Undergone Bone Marrow Transplantation. (3rd December 2013) - Accardo, Jennifer; De Lisi, Domenico; Lazzerini, Paola; Primavera, Alberto
Abstract : In anoxic coma, myoclonic status epilepticus and other nonreactive epileptiform patterns are considered as signs of poor prognosis. We report the case of a good recovery in a prolonged comatose myoclonic status epilepticus (MSE) after a cardiac arrest (CA) treated with mild therapeutic hypothermia (TH) in a patient who had undergone a bone marrow transplantation for Hodgkin's lymphoma. This case emphasizes the opportunity of performing an electroencephalogram (EEG) in the acute period after an hypoxic-ischemic insult and underlines the diagnostic difficulties between MSE and Lance-Adams syndrome, which classically occurs after the patient has regained consciousness, but can also begin while the patient is still comatose or sedated. Major problems in prognostication for postarrest comatose patients will also be pointed out.